Empirical study of multidimensional Child-Langmuir law with plasma ion source extraction using round apertures. Issue 1 (1st April 2022) - Kosonen, S T; Kalvas, T; Tarvainen, O; Toivanen, V
Abstract: One dimensional Child-Langmuir (CL) law is commonly used in ion source physics to describe space charge limited ion extraction from the plasma. Recently 2D and 3D CL laws have been derived, but plasma ion extraction does not strictly meet the assumptions in these CL laws. Investigations on the applicability of the CL laws to ion source extraction were conducted using filament-driven ion source, measuring the beam currents as a function of extraction voltage. The experiments are complemented with simulations where IBSimu is used for studying the behaviour of plasma meniscus. Three different voltage regions were identified with low, moderate and high voltage. With moderate voltages the extracted beam current density shows signs of 3D CL law. The results indicate that for the total beam current CL laws are not valid but instead require collimation for the CL effects emerge.